Classification Of Student Mental Health Based On Academic And Social Variables Using The Decision Tree Method - Anggreani, Desi; Danuputri, Chyquitha; Hayat, Muhyiddin A M; Setiawan, Dedi (Jurnal Algoritma, Logika dan Komputasi, 2025)
Mental health problems are suffered by many people, including students who often have poor lifestyles. Depression and anxiety are widespread among students, with all universities reporting students with depression and 75.5% reporting students with severe anxiety. This research aims to determine the classification of student mental health based on academic and social by using the Decision Tree method so that early treatment can be carried out. The dataset used consists of 11 aspects concerning academic and social. The data that has been collected is processed through the preprocessing stage and analyzed using the Decision Tree classification method. The classification results showed that out of 973 students who did not suffer from depression, the method classified them correctly. In addition, of the 104 college students who were classified as suffering from major depression, all of them were actually suffering from major depression. The agreement between the classification results and the actual condition shows the reliability of this method, with an accuracy rate of 76.71%. This research underscores the importance of academic and social variables in influencing students' mental health. The findings confirm the reliability of the Decision Tree method in detecting students' mental state and point to the need for effective counseling services and mental health interventions in campus and social environments.